Evaluating the Effectiveness of Competency-Based Didactic Approach (CBDA) in Pediatric Nursing Education: A Mixed-Method Study - Amal Murad; Eman Mater (Nursing Research and Practice)
Competence-Based Didactic Approach (CBDA) supported students in developing their ability to integrate knowledge, skills, and attitudes. The study aimed to evaluate the effectiveness of CBDA in pediatric nursing education by establishing a CBD Model (CBDM) and examining the nursing students’ scores and grades. The exploratory sequential mixed methods research design was used to explore the CBDM and its effect on the students’ performance through their scores. Six hundred eighteen undergraduate nursing students were involved in the study. Purpose sampling was adopted to identify the CBDA impact on the nursing students score and grades. CBDM was established in parent and child nursing course to emphasize the application of didactic principles with nursing competencies. Study findings proved the highly nursing performance of CBDA among undergraduate nursing students’ scores and grade. The comparison of students’ scores between traditional and CBDA groups (two and three semester system) revealed highly statistically significant improvement (p < 0.001) which justified the research hypotheses of CBDA implementation. The total average of student scores increased from 84.54 ± 3.21 in the traditional group to 88.29 ± 1.59 in the CBDA groups. In addition to the improvement of communication skills which increased from 3.83 ± 0.36 in traditional groups to 5.88 ± 0.22 in CBDA groups. CBDA improved students’ performance by emphasizing their active participation in the learning processes through the application of didactic principles in the nursing education with clear plans that clarified teaching strategies and assessment methods. CBDM is more applicable in nursing courses and improve learning outcomes and curriculum design.